Limb ischemic preconditioning attenuates cerebral ischemic injury in rat model. (May 2014) - Wang, W; Yu, XD; Mo, X; Zhang, HB; Zhu, DM
Ischemic brain injury is not uncommon after open-heart surgery with cardiopulmonary bypass and seriously undermines the patients' life quality. Therefore, potential protective effects of limb ischemic preconditioning (LIP) on subsequent ischemic injury of the brain were investigated by evaluating anti-inflammatory effects and apoptosis of pyramidal neurons in the CA1 hippocampus. One hundred and eight Sprague-Dawley rats were divided into the middle cerebral artery occlusion (MCAO) group (n=54) and the LIP group (n=54). A thread was used to occlude the middle cerebral artery in the MCAO group and the LIP group animals were pretreated with LIP followed by MCAO. In the two groups, nine samples were collected at each time-point of 0, 6, 12, 24, 48 and 72 h after MCAO to detect IL-6 and IL-17 and their mRNA levels. Neurological severity scores (NSS) were examined before the animals were sacrificed. Compared with the LIP group, cerebral histopathological changes in the MCAO group were most distinct and significantly more infiltrated inflammatory and apoptotic neuronal cells were observed at 24, 48 and 72 h post-surgery. IL-17 and IL-6 mRNA levels analyzed by quantitative real-time polymerase chain reaction (PCR) (qRT-PCR) were significantly reduced in the LIP group compared with the MCAO group at the 12, 24 and 48 h time-points. A significant reduction in IL-17 expression level was determined by enzyme-linked immunosorbent assay (ELISA) in the LIP group at 12, 24 and 48 h, while IL-6 was significantly reduced at the 24 and 48 h time-points. The NSSs were not significantly different between the groups. Therefore, in a MCAO rat model, we have proved that LIP pretreatment can protect the brain from infarction after ischemic injury and induce ischemic tolerance, potentially, by reducing IL-17 to provide anti-inflammatory effects and attenuate apoptosis of hippocampal neuronal cells.